Energy spectra of sputtered ions: assessment of the instrumental resolution. (24th February 2012) - Gnaser, Hubert
Abstract : The energy spectra of Cs + ions sputtered from silicon under 5.5‐keV Cs + bombardment were recorded for emission energies E  ≤ 100 eV. The emitted ions were detected in a high‐sensitivity double‐focusing SIMS (Cameca IMS‐4f). The influence of several instrumental parameters on the energy resolution and the peak position of the measured spectra were investigated to determine the instrument's resolution response. Specifically, entrance apertures with four different diameters (410, 280, 50, and 25 µm) were used in the energy analyzer, whereas the width of its exit slit was varied from 3300 to 15 µm. For the smallest of these values, the full width at half maximum (FWHM) of the Cs + spectrum amounts to 2.2 eV. A box‐type resolution function was found to describe the energy distributions over a substantial range. Using that function, the Cs + distributions measured for various slit settings can be reproduced via the convolution of a single original function. The values of the spectral width obtained from this procedure are essentially identical with the FWHM values of the recorded spectra. Copyright © 2012 John Wiley & Sons, Ltd.